Diaparsis phobos sp. nov. and D. deimos sp. nov., two amazing new species of Tersilochinae (Hymenoptera: Ichneumonidae) from Madagascar - Khalaim, Andrey I. (Zootaxa, 2021)
Two species of the genus Diaparsis Förster, D. phobos sp. nov. and D. deimos sp. nov., are described from Madagascar. The genus Diaparsis, as well as the subfamily Tersilochinae, is recorded from Madagascar for the first time. Both new species possess unuque morphological features previously unknown in the subfamily Tersilochinae: D. deimos sp. nov. has a remarkable slightly decurved ovipositor, and D. phobos sp. nov. possesses deep impressions on outer sides of ocelli.